EMOSI TOKOH DALAM NOVEL AKU, BENCI, DAN CINTA KARYA WULANFADI TINJAUAN PSIKOLOGI SASTRA - Putri Oktarilla Murti; Antonius Totok Priyadi; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis research was motivated to find the emotions of characters in the novel Aku, Benci, dan Cinta by Wulanfadi. The problem in this research was how the emotions of the characters in the novel Aku, Benci, dan Cinta by Wulanfadi, and the learning level of Indonesian language of high school students. This study aims to analyze these problems. Theories used in this study include: emotions, types of emotions, novels, behavioristic psychology, literary learning in schools, and learning plans. The method used in this research was descriptive method with a qualitative form of research that used a behavioristic psychology approach. Data sources used are novel Aku, Benci, dan Cinta by Wulanfadi and data in the form of positive emotions and negative emotions in the form of quotes, words or sentences. In this research the data collection technique used in the form of documentary studies and tools used in the form of researchers themselves. The data validity testing technique used was adequacy of references and triangulation. The data analysis technique used was content analysis. The results of this study about the emotions of characters in the novel in the form of (1) positive emotions ; (2) negative emotions ; (3) the emotion implementation of the characters in the novel used as Indonesian language learning material for high school to the XII class students from the aspect of curriculum, literary learning objectives, selection of teaching materials, and readability. The results of this study are expected to be used by teachers as teaching material in schools and this research can provide input for further researchers to use novel Aku, Benci, dan Cinta by Wulanfadi. Keywords: Emotion, Character and Novel